Muzikoterapija - Celarec, Vida (Obzornik zdravstvene nege, 1981)
Musicotherapy used in the Centre for Treatment of Alcoholism, Škofljica, is based on the finding that tension, relaxattion and contentment constiture the essential components of music experience. The patients included in musicotherapy get a better insight into their own emotional world. Feeling more secure, they find it easier to express their emotions than during other therapeutic classes. To illustrate this finding the author deals with joy of listening to the musical works of Beethoven, Bach, Hačaturjan and Strawinski. Therapeutic procedures adapted to the selected music and group dynamics require wide knowledge of music psychology and great skill of the therapist engaged in the psychotherapeutic group activity.